Penerapan Pendidikan Karakter Berbasis Kearifan Lokal Di Madrasah Ibtidaiyah Negeri 1 Merangin - M. Zhaharil Fikri (Jurnal Pendidikan Indonesia, 2022)
The study of this journal aims to determine the cultivation of character education based on local wisdom in Madrasah Ibtidaiyah Negeri 1 Merangin. This research is in the form of a qualitative description, namely data collection by direct observation method which is analyzed using data reduction, data display and drawing conclusions. The planting can be found in the following cases: 1. Through the learning process, especially in the mulok subjects, arts, culture and regional languages. 2. Through the process of extracurricular activities such as sports, dance and scouts. 3. Through an exemplary process, namely with exemplary attitudes that are exemplified by all stakeholders in MIN 1 Merangin. 4. Through the habituation process, it can be seen from the habit of students and teachers greeting each other when they meet who applies smiles, greetings and greetings. 5. Through the conditioning process, which is marked by the presence of slogans, posters that show the local culture and language.